Coco e cocar: lutas, resistências e identidades compartilhadas das indígenas e quebradeiras de coco Akroá Gamella em Viana, Maranhão - Muniz, Ariana Gomes da Silva (2023)
This research highlights the struggle shared by indigenous women and babassu coconut breakers from the Taquaritiua territory, in the municipality of Viana, Maranhão. It aims to analyze and describe its processes of struggle and organization with its people, as well as the production practices and resumption of territories for environmental preservation.Through an ethnographic report, the evolved interethnic relations and the use of guarimã and babassu agroextractivism were considered to demarcate the differentiation between collectivities and understand issues of the territory, retakes and mutirão.It should be noted that the struggle shared with allies was strengthened after a period of (forced) silencing of an ethnic identity, evidencing the resistance waged to maintain the lives that remain in this ancestral territory since the second half of the 18th century, but whose extinction was decreed by the Brazilian state. The ethnographic reports show that the struggle is constant and characterize a people of great resistance to the various attempts at exploitation and violence since the colonization process. The work was structured from the relationship built by the researcher with the territory, started even before the master's degree, through which it was possible to apprehend reports and information. This experience made it possible to accompany, together with the Akroá Gamella, a moment of increasing violence against them by antagonists in the various instances that structure and strengthen racism, negligence and attempts at dehumanization.